Muscle-derived factors influencing bone metabolism. (March 2022) - Gries, Kevin J.; Zysik, Victoria S.; Jobe, Tyler K.; Griffin, Nicole; Leeds, Benjamin P.; Lowery, Jonathan W.
Abstract: A significant amount of attention has been brought to the endocrine-like function of skeletal muscle on various tissues, particularly with bone. Several lines of investigation indicate that the physiology of both bone and muscle systems may be regulated by a given stimulus, such as exercise, aging, and inactivity. Moreover, emerging evidence indicates that bone is heavily influenced by soluble factors derived from skeletal muscle (i.e ., muscle-to-bone communication). The purpose of this review is to discuss the regulation of bone remodeling (formation and/or resorption) through skeletal muscle-derived cytokines (hereafter myokines) including the anti-inflammatory cytokine METRNL and pro-inflammatory cytokines (e.g., TNF-α, IL-6, FGF-2 and others). Our goal is to highlight possible therapeutic opportunities to improve muscle and bone health in aging.